Migrasi Sirkuler dan Status Sosial Masyarakat Perdesaan Jawa Kasus di Dusun Trukan Kabupaten Gunung Kidul. - Eko Murdiyanto (Jurnal Dinamika Sosial Ekonomi, 2004)
The circular migration sympton happened in Trukan related to bod natural condition especially unproductive land. Circular migration process on a part of village people not only to develop household economy but also the increase the social status of migran family. These impact to the people soth kau social status to migrate in onder to rise they social status in contrast, in fact circular migrution ale dal by society with high status. These case show that migration in Trukan region in a fe style, not just to economy recovered Keyword: circular migration, social states he style